Experimental Study of Phase Entrainment in Copper Solvent Extraction• [Estudio Experimental de Atrapamiento de Fases en Extracción por Solventes de Cobre] - Navarro-Donoso, P; Vargas-Riquelme, C (Universidad Nacional de Colombia, 2020)
The entrainment of the organic phase in the aqueous applied to typical solutions in a copper solvent extraction process was studied. The organic phase used is composed of the commercial extractant LIX 984-N diluted in Shellsol 2046 AR. The aqueous phase contains 6 g/L of Cu2+, at pH 2 and 20 ºC. The variables studied were: mixing speed of 400 to 1000 rpm; mixing time of 3 to 30 minutes; initial pH of the electrolyte 2, 3, and 4; percentage of extractant in the organic phase 10 to 30% v/v; and copper concentration in the aqueous phase 1 to 6 g/L. It was determined that the entrainment of the organic phase in the aqueous is determined by the physical properties of the phases in equilibrium and by the system’s hydrodynamics, and it is a phenomenon that involves the advancing speed of the interphase (or dispersion band) and the displacement speed of the organic drops. © The author; licensee Universidad Nacional de Colombia.